Best trigonometric and bilinear approximations for the Besov classes of functions of many variables - Romanyuk, A. S.; Романюк, А. С.; Романюк, А. С. (Institute of Mathematics, NAS of Ukraine, 1995)
We obtain order estimates for the best trigonometric and bilinear approximations for the classesB p,θ r of functions of many variables.